Structural Optimizations of a 12/8 Switched Reluctance Motor using a Genetic Algorithm - Sholahuddin, Umar; Purwadi, Agus; Haroen, Yanuarsyah (Unijourn Publisher, 2018)
Structural design optimization of 12/8 switched reluctance motor using single objectives genetic algorithms is explored. The objective of this optimization is to maximize the output torque using four parameters, namely rotor width of tooth root, rotor width of tooth tip, half of stator tooth width, and stator outer diameter. The result is the optimized motor has higher average torque of 25% compared to the initial design. The evaluation of motor model is finite element method. The 12/8 switched reluctance motor will be applied in a mini electric vehicle.